Impact of COVID-19 on training: a single-centre survey of trainees - Thomas Whitby; Gavin Cleary; Clare P Halfhide (BMJ Publishing Group, 2020)
To review the impact of COVID-19 on postgraduate paediatric training, a 10-question online survey was designed to evaluate trainees' training opportunities. 56 trainees working at a single centre, Alder Hey Children's Hospital, completed the survey. The majority of trainees felt that COVID-19 had affected their training. Trainees wanted to become involved in Quality Improvement Programs. Face-to-face teaching was still favourable but web-based teaching methods were preferred. Novel online, Worked Based Assessment clinics were well received. COVID-19 has affected traditional learning opportunities but offered a new positive range of digital solutions to give and store educational material.